Первые иллюстраторы произведений Л. Н. Толстого : [М. С. Башилов, Л. О. Пастернак : альбом] / авт.-сост. Т. Поповкина, О. Ершова - Поповкина Татьяна Константиновна (Изобразительное искусство, 1978)
Экземпляры: ИСК (20111201) / Инвентарный номер: 682946 / Цена: 3.10 / Сис.шифр: 85.153(2)-8 / Авт.знак: П 26 / ГРНТИ: 18 / ББК: 85.153(2=Рус)1-8